drawback
Dec 10, 2020

answers: 1

Register to add an answer

The time for answering the question is over

Answer:

Step-by-step explanation:If x³ - 3x² + 3x - 7 = (x + 1)(ax² + bx + c), then find (a + b + c)

first multiply

(x + 1)(ax² + bx + c)

= ax³ + bx² + cx + ax² + bx + c

= ax³ + bx² + ax² + cx + bx + c

= ax³ + (b+a)x² + (c + b)x + c

comparing it with

x³ - 3x² + 3x - 7

a = 1

b + a = -3 => b + 1 = -3 => b = -4

c + b = 3 = > c - 4 = 3 => c = 7

c = -7 should be 7

as if we put x = -1 in

x³ - 3x² + 3x - 7

-1 - 3 - 3 - 7 = 14 so x + 1 can not be factor so x +1 will be factor if

x³ - 3x² + 3x - 7 is actually

x³ - 3x² + 3x + 7

then -1 - 3 - 3 + 7 = 0

hence we can say that

a = 1

b = -4

c = 7

so a + b + c = 4

446

Pekka

Dec 10, 2020

For answers need to register.

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions